2023
DOI: 10.1021/acs.analchem.3c03998
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of the Confused Complex in Oxidation of 3,3′,5,5′-Tetramethylbenzidine for the Reliable Chromogenic Bioassay

Caixia Zhu,
Hong Yang,
Xuwen Cao
et al.

Abstract: Regulation of the reaction pathways is a perennial theme in the field of chemistry. As a typical chromogenic substrate, 3,3′,5,5′-tetramethylbenzidine (TMB) generally undertakes one-electron oxidation, but the product (TMB ox1 ) is essentially a confused complex and is unstable, which significantly hampers the clinic chromogenic bioassays for more than 50 years. Herein, we report that sodium dodecyl sulfate (SDS)-based micelles could drive the direct two-electron oxidation of TMB to the final stable TMB ox2 . … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…27−29 Colorless TMB can be oxidized to form blue product (oxTMB) by some reactive oxygen species. 29,30 Recent studies revealed that surface Ov can serve as the absorption site of H 2 O 2 or dissolved O 2 , and then H 2 O 2 or dissolved O 2 reacts with the trapped electrons on the metal oxide surface to produce some active oxygen species. 31 For example, the surface Ov of ZnO could serve as the active site for transformation of H 2 O 2 into a hydroxyl radical ( • OH), 32 and the surface Ov of TiO 2 could convert the dissolved O 2 to a superoxide anion radical (O 2…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…27−29 Colorless TMB can be oxidized to form blue product (oxTMB) by some reactive oxygen species. 29,30 Recent studies revealed that surface Ov can serve as the absorption site of H 2 O 2 or dissolved O 2 , and then H 2 O 2 or dissolved O 2 reacts with the trapped electrons on the metal oxide surface to produce some active oxygen species. 31 For example, the surface Ov of ZnO could serve as the active site for transformation of H 2 O 2 into a hydroxyl radical ( • OH), 32 and the surface Ov of TiO 2 could convert the dissolved O 2 to a superoxide anion radical (O 2…”
Section: ■ Introductionmentioning
confidence: 99%
“…A colorimetric method is frequently regarded as a popular measurement technique due to its simplicity, convenience, and low cost. , Without the aid of any other advanced facilities, the colorimetric method is suitable for field analysis and point-of-care test. As one classic chromogenic regent, 3,3′,5,5′-tetramethylbenzidine (TMB) features specific interest because of its high response sensitivity and low toxicity. Colorless TMB can be oxidized to form blue product (oxTMB) by some reactive oxygen species. , Recent studies revealed that surface Ov can serve as the absorption site of H 2 O 2 or dissolved O 2 , and then H 2 O 2 or dissolved O 2 reacts with the trapped electrons on the metal oxide surface to produce some active oxygen species . For example, the surface Ov of ZnO could serve as the active site for transformation of H 2 O 2 into a hydroxyl radical ( • OH), and the surface Ov of TiO 2 could convert the dissolved O 2 to a superoxide anion radical (O 2 •– ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation